1998
DOI: 10.1098/rspa.1998.0288
|View full text |Cite
|
Sign up to set email alerts
|

Observation and measurement of an optical Aharonov–Albert–Vaidman effect

Abstract: The notion of the weak value of a quantum mechanical observable has recently been introduced by Aharonov et al ., hereafter referred to as AAV. Their analysis led to the controversial result that the weak values for an observable can lie well outside its associated eigenvalue spectrum. We have performed an experiment similar to one proposed by Knight et al . and demonstrated that weak values can be observed and that they exhibit the properties described by AAV within the regime of validity defined by Duck et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 14 publications
2
90
0
Order By: Relevance
“…The relevance of (2.8) and (2.9) is that indeed the weight of a PPME measurement outcome distribution need not lie within the "normal" region of expectation defined by the bounds of the spectrum of ( Fig.1), contrary to what one would have naively expected given the generality of the spectral expansion of the PME distribution (2.3). This may not be obvious under strong measurement conditions, such that when the appartus wave function in p is expanded as a superposition of shifted wave functions 10) the overlap between two shifted functions φ(p − a) and φ(p − a ′ ) for all a = a ′ is negligible. Indeed, in such a case, the resulting p.d.f.…”
Section: Pre-and Postselected Measurement Statistics Eigenvaluesmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of (2.8) and (2.9) is that indeed the weight of a PPME measurement outcome distribution need not lie within the "normal" region of expectation defined by the bounds of the spectrum of ( Fig.1), contrary to what one would have naively expected given the generality of the spectral expansion of the PME distribution (2.3). This may not be obvious under strong measurement conditions, such that when the appartus wave function in p is expanded as a superposition of shifted wave functions 10) the overlap between two shifted functions φ(p − a) and φ(p − a ′ ) for all a = a ′ is negligible. Indeed, in such a case, the resulting p.d.f.…”
Section: Pre-and Postselected Measurement Statistics Eigenvaluesmentioning
confidence: 99%
“…The usefulness of this description has been demonstrated, both theoretically and experimentally, in a number of applications in which novel aspects of quantum processes have been uncovered when analyzed in terms of * Electronic address: abotero@uniandes.edu.co weak values. These include photon polarization interference [7,8,9,10,11], barrier tunnelling times [12,13,14], photon arrival times [15,16], anomalous pulse propagation [17,18,19], correlations in cavity QED experiments [20], complementarity in "which-way" experiments [21,22], non-classical aspects of light [23,24], communication protocols [25] and retrodiction "paradoxes" of quantum entanglement [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…A classical optical analog [6] of the original experiment proposed by AAV has been realized experimentally [7]. The polarization state of a classical radiation field can be treated as analogous to a spin-1 2 system, and the weak value of polarization may exceed the eigenvalue range [8,9]. It has also been found that weak values have applications within classical optical communication [10,11].…”
mentioning
confidence: 99%
“…While the interpretation of weak values remains somewhat controversial, several of the unusual properties predicted by weak value theory have been experimentally verified, e.g. [4][5][6].…”
Section: Introductionmentioning
confidence: 99%